2013
DOI: 10.1007/s11096-013-9834-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot study to influence medication adherence of patients with diabetes mellitus type-2 by the pharmacy

Abstract: The 'Support for Diabetes' intervention is feasible to implement in pharmacy practice. Poor co-operation between pharmacists and GPs and lack of re-imbursement are obstructions for implementation on a wider scale. These issues should receive attention of pharmacists, policymakers and researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In this implementation, the systematization of actions and the uptake of the team were important to envision the maintenance of the program in a long-term perspective. This is aligned with the literature [ 10 , 12 ]. Despite the encountered barriers, healthcare professionals continued to deliver the program and wanted to extend it to other pathologies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this implementation, the systematization of actions and the uptake of the team were important to envision the maintenance of the program in a long-term perspective. This is aligned with the literature [ 10 , 12 ]. Despite the encountered barriers, healthcare professionals continued to deliver the program and wanted to extend it to other pathologies.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of motivation and the lack of benefits perceived by healthcare professionals are barriers that limit the adoption of these new services [ 2 , 8 , 11 ]. Moreover, external factors such as the patients’ needs and acceptance/perception, the lack of collaboration, and the opinion of other healthcare professionals also influence the implementation of new services [ 8 , 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,25,26 Seven studies evaluated the use of pharmacy technicians in advanced roles and as part of team-based interventions. [27][28][29][30][31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…Although no studies have specifically evaluated the role of pharmacy technicians in onychomycosis treatment, other studies have shown the benefits of utilizing pharmacy technicians for improving outcomes in other disease states, such as hypertension and diabetes. 29,30 Pharmacy technicians can identify patients at risk for poor adherence and adverse reactions. [29][30][31] The use of a team approach involving pharmacy technicians can improve refill rates and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…This overview can be used as an action plan. The intervention programme and materials are partly based upon the promising results of a previous study in which the feasibility of a modular intervention programme in patients with diabetes was evaluated [29]. On top of that, the intervention materials (the QBS and the TIG) were further developed based upon our own research including a systematic literature review and a cross-sectional study (manuscripts in preparation).…”
Section: Methodsmentioning
confidence: 99%